Recent Preclinical Insights Into the Treatment of Chronic Traumatic Encephalopathy - Breen, Patrick W.; Krishnan, Vaishnav (Frontiers in Neuroscience, 2020)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative condition associated with significant mortality and morbidity. The central pathophysiological mechanisms by which repetitive cranial injury result in the neurodegeneration of CTE are poorly understood. Current well-established working models emphasize the excessive phosphorylation and subsequent accumulation of insoluble tangles of Tau protein. In this review, we briefly review data from preclinical animal models of CTE where a series of candidate treatments for CTE have been carefully evaluated, including kinase inhibitors, antibody therapy, and anti-inflammatory therapies. We discuss their translational potential and provide recommendations for future bench to bedside strategies.